Correction to: Melanin‑concentrating hormone and orexin shape social affective behavior via action in the insular cortex of rat. - Barretto‑de‑Souza, Lucas; Joseph, Shemar A.; Lynch, Francesca M.; Ng, Alexandra J.; Crestani, Carlos C.; Christianson, John P. (Psychopharmacology, 2025)
The article addresses a correction made to a previously published manuscript in the field of psychopharmacology, specifically noting that asterisks indicating significant differences in Figures 4 and 5 were not displayed in the original version. The correction has been officially issued to rectify this oversight. The publisher, Springer Nature, maintains a neutral stance regarding jurisdictional claims in published maps and institutional affiliations.